Laser decontamination and decomposition of PCB-containing paint. (January 2017) - Anthofer, A.; Kögler, P.; Friedrich, C.; Lippmann, W.; Hurtado, A.
Abstract: Decontamination of concrete surfaces contaminated with paint containing polychlorinated biphenyls is an elaborate and complex task that must be performed within the scope of nuclear power plant dismantling as well as conventional pollutant cleanup in buildings. The state of the art is mechanical decontamination, which generates dust as well as secondary waste and is both dangerous and physically demanding. Moreover, the ablated PCB-containing paint has to be treated in a separate process step. Laser technology offers a multitude of possibilities for contactless surface treatment with no restoring forces and a high potential for automation. An advanced experimental setup was developed for performing standard laser decontamination investigations on PCB-painted concrete surfaces. As tested with epoxy paints, a high-power diode laser with a laser power of 10 kW in continuous wave (CW) mode was implemented and resulted in decontamination of the concrete surfaces as well as significant PCB decomposition. The experimental results showed PCB removal of 96.8% from the concrete surface and PCB decomposition of 88.8% in the laser decontamination process. Significant PCDD/F formation was thereby avoided. A surface ablation rate of approx. 7.2 m 2 /h was realized. Highlights: Development of a laser decontamination system with simultaneous decomposition. Experiments with a 10 kW high-power diode laser in continuous wave (cw) mode. Interaction between laser parameters, quality of concrete and PCB-concentration. Comparison between laser removal of epoxy paints and PCB-containing paints. PCB decontamination rates of 97% and PCB decomposition rates of 89%.